‘I should like to see a woman smoking while she was nursing her baby’: The New Woman, Crossdressing, and Humour in Horace William Bleackley’s Une Culotte (1894) - Mariam Zarif (Cahiers Victoriens et Edouardiens)
While the New Woman was often mocked and caricatured as a mannish and destructive figure in the late Victorian press, New Woman writers also used humour to attack the status quo and parry ridicule with ridicule. A case in point is the non-canonical New Woman novel, Une Culotte; or a New Woman, An Impossible Story of Modern Oxford (1894), by Horace William Bleackley. This essay explores the fundamental contradictions of humour in Une Culotte by looking at how Bleackley situates his New Women heroines within the context of nineteenth-century British feminism. First I suggest that humour is generated in the novel by the New Woman protagonist’s comic attacks of the rigid construction of gender differences. Then I examine how as a male New Woman writer Bleackley successfully uses female cross-dressing to humorous effect in order to empower the New Woman with opportunities that extend beyond the parameters of home. Bleackley incorporates comic mockery to expose the gender pretensions of the period and ultimately celebrates the New Woman’s control of their bodies. In Une Culotte, the New Women fight back against the mockery of the deeply-rooted culture of contempt for progressive women whilst revealing the comic dimension of cross-dressing and its threat to a dichotomous culture of gender and sexuality.